Formation of laterally-oriented monolayers of plasmonic silver nanoplats and their ensembles with cadmium selenide quantum dots on the sur face of thin polymeric film - Malakhovsky, Pavel O. (Journal of the Belarusian State University. Chemistry, 2019)
We present here a novel method for formation of laterally-oriented monolayers of plasmonic silver nanoplates and their electrostatic ensembles with semiconductor quantum dots. Monolayers were electrostatically deposited on the surface of thin polymeric film containing different amount of tertiary amino groups. This method allows simultaneously investigate optical properties and morphology of silver nanoplates using transmittance electron microscopy. The optical density of films and surface concentration of silver nanoplates is proportional to the percentage of tertiary amino groups in the polymeric film. A surface ligand exchange was used for functionalization of the surface of silver nanoplates toward formation of electrostatic ensembles with colloidal quantum dots. We observed a straight correlation between the red shift of surface plasmon resonances in silver nanoplates and alkyl chain length of ligand molecules.